EXAMINING THE DETERMINANTS OF POVERTY IN EAST JAVA - Kholifah, Dewi; Sumarsono, Hadi (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: Economic development is one of a nation's attempts to achieve social well-being. The poverty line could possibly be utilized to indicate social welfare given there is an adverse relationship between welfare and poverty rates in Indonesia. A citizen is considered to be poor if their earnings are insufficient to cover necessities such food and shelter. Methods: This research uses the panel data method in 38 districts/cities in East Java Province between 2019 and 2022. Results: Economic growth, general allocation funds, and health have a negative and substantial impact on the poverty rate of districts and cities in East Java Province. Conclusion and suggestion: The government is expected to be able to maximize the results of the economic sector in each district or city in East Java, due to a high potential for expanding the economy, in addition to optimizing general allocation funds for public infrastructure and facilities, access to education, health, and infrastructure that stimulates economic activity, and enhance the quality of public health considering good health, of course, leads to economic growth.